The Effect of Transplantation of Tissue‐Engineered Cell‐Sheets after Middle Ear Surgery in a Rabbit Model. (2nd September 2014) - Yamamoto, Kazuhisa; Kojima, Hiromi; Yaguchi, Yuichiro; Hama, Takanori
Abstract : Objectives: Postoperative regeneration of the middle ear mucosa and pneumatization of the middle ear cavity are of great importance after middle ear surgery. This study developed a new method to transplant autologous nasal mucosal epithelial cell‐sheets into the damaged middle ear cavity. The aim of this study was to evaluate postoperative healing after the transplantation of the cell sheets in rabbits. Methods: Rabbit nasal mucosal epithelial cell‐sheets were fabricated from a temperature‐responsive culture dish and transplanted into the damaged middle ear of the rabbit, which was surgically created. The healing of middle ears was evaluated with histological methods and computed tomography findings at 8 weeks after transplantation. Functional evaluation was performed by measuring the maximum middle ear total pressure reflecting a trans‐mucosal gas exchange function. Two control groups were used: the normal control group and the mucosa‐eliminated control group. Results: Transplantation of nasal mucosal epithelial cell‐sheets suppressed the bone hyperplasia and the narrowing of pneumatic space in the middle ear cavity more clearly than the mucosa‐eliminated control group. The mucosal gas exchange function was also found to be good in the cell sheet‐transplanted group. These results suggest that posttransplanted middle ear cavity is not only morphologically but also functionally similar to the normal middle ear cavity. Conclusions: Nasal mucosal epithelial cell‐sheet is confirmed to be useful as an effective graft material after middle ear surgery, and will hopefully become a novel therapy in the future.